Internet of Things and machine learning in agriculture technological impacts and challenges - Jain, Vishal, 1983-; Chatterjee, Jyotir Moy; Kumar, Abhishek; Rathore, Pramod Singh, 1988- (De Gruyter frontiers in computational intelligence, 2021)
Agriculture is one of the most fundamental human activities. As the farming capacity has expanded, the usage of resources such as land, fertilizer, and water has grown exponentially, and environmental pressures from modern farming techniques have stressed natural landscapes. Still, by some estimates, worldwide food production needs to increase to keep up with global food demand. 'Machine Learning and the Internet of Things' can play a promising role in the Agricultural industry, and help to increase food production while respecting the environment. This book explains how these technologies can be applied, offering many case studies developed in the research world.